Strategi Manajemen Sumber Daya Manusia (SDM) untuk Memberikan Pelayanan Prima pada Politeknik Piksi Input Serang - Siti Sofiyah; Yeti Asmawati; Yanto Heryanto; Dian Evariana (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Human resource development is a process of how management gains experience, skills and attitudes to achieve success as leaders in the organization, so that development activities are aimed at helping employees/employees to be able to handle their responsibilities in the future. Bearing this in mind, training and human resource development programs are needed which are carried out periodically and continuously, in order to provide satisfactory (prime) service. Thus, companies/institutions need to have good operational implementation instructions, as well as educated officers who can implement these operational systems and procedures appropriately. Apart from development, training activities are also very influential on human resources because with this training human resources will be encouraged to be able to provide excellent service for candidates or those interested in buying or using their services. And it is no less important to provide training to customer service on how to serve in a very friendly, polite, knowledgeable manner so that clients/interested people can feel comfortable when communicating or making transactions.